Efficacy of intermaxillary fixation screws - Biswas, KP; Ahuja, A; Singh, VP (Health Renaissance, 2012)
Intermaxillary fixation (IMF) is a technique which is basically used for management of fracture.This includes IMF screws and various dental wirings. However IMF may not be advantageous in case of edentulous or partially dentulous patients. The purpose of this article is to report a case of unilateral parasymphyseal and zygomatic arch fracture managed successfully by IMF screws and to list the difficulties faced during the surgery. DOI: http://dx.doi.org/10.3126/hren.v10i1.6013 HREN 2012; 10(1): 69-71